Mengkritisi Ajaran Hyper Grace - Yunus Ompusunggu (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2020)
The concept of salvation in Christian theology is a crucial teaching. After the reformation of the church in the 16th century, the doctrine of